The Chinese version of the physical activity questionnaire for adolescents: a psychometric validity, reliability, and invariance study - Ling Qin; Walter King Yan Ho; Selina Khoo (BMC, 2024)
Abstract Background The Physical Activity Questionnaire for Adolescents (PAQ-A) is one of the most commonly used questionnaires for assessing adolescents' levels of moderate to vigorous physical activity (PA). Although a Chinese version of the PAQ-A (comprising nine items) exists, it has been assessed for only internal consistency coefficients, test-retest reliability, and correlations with the GT3X + accelerometer. Therefore, this study aimed to evaluate the psychometric properties of the Chinese version of the PAQ-A among Chinese adolescents. Methods This study included three samples of 1,101 secondary school students (12-19 years old). The first sample consisted of 518 participants (50.4% males, 49.6% females) for correlation tests and exploratory factor analysis (EFA). The second sample consisted of 227 participants (55.75% males, 44.24% females) for confirmatory factor analysis (CFA), convergent validity, and sample size invariance tests. The third sample consisted of 356 participants (54.50% male, 45.50% female) for the internal consistency reliability test, invariance test (cross sample size, education level and gender), and t-test. Results Pearson correlation analysis of the PAQ-A indicated that all the total-item correlations exceeded 0.2, indicating good consistency across the items. Subsequent EFA of the Chinese version of the PAQ-A revealed a two-factor structure. CFA subsequently validated this structure. One of the items exhibited a standardized loading below 0.4 and was excluded. The exclusion of this item resulted in increased standardized loadings for the remaining items, ranging from 0.40 to 0.82, which indicates improved fit indices. This adjustment underscores the questionnaire's satisfactory convergent validity and robust discriminant validity. The overall Cronbach's alpha was 0.821, with the values for the first and second factors being 0.757 and 0.716, respectively. The questionnaire demonstrated stable invariance across sample sizes and education levels and additionally showed partial scalar invariance across genders. A t-test revealed a significant difference between males and females, which aligns with previous findings. These findings supported the construct validity of the questionnaire. Conclusion This study validated the Chinese version of the PAQ-A for assessing adolescent PA in China, with a two-factor structure improved by removing one item.